Micro hardness and corrosion properties of A390 alloy + x vol.% zirconium dioxide (ZrO2) composites processed by P/M method. (17th October 2019) - Karthikeyan, S.; Subramanian, M.; Ghosh, Ashoke; Prashanth, M.; Karunanithi, R.
A390+X vol.% ZrO2 (X = 5, 10, 15) composites have been fabricated through P/M technique. The mixed aluminium alloy and zirconium oxide powders were cold compacted at 200 MPa and sintered at 580°C for 3 h. The influence of ZrO2 reinforcement on microstructure, physical, and electrochemical behaviour of fabricated composites were examined. The results convey that the composites have relative density of 99%. Potentio dynamic polarisation studies on A390 and A390+Xvol.% ZrO2 composites in 3.5 wt.% of NaCl solution revealed that the addition of ZrO2 in Al alloy shifts the corrosion potentials towards positive direction. The increase of ZrO2 content in A390 alloy increases the corrosion current density due to the expansion in particle-matrix interface area. The research goal is to develop a new metal matrix composite material, by powder metallurgy (P/M) technique and experimentally investigate the various mechanical, physical properties and corrosion study, for ensuring that the developed material could be used in pistons.